The Role of HTA for Essential Health Benefit Package Design in Low or Middle-Income Countries - Ole F. Norheim; David A. Watkins (Taylor & Francis Group, 2023)
This Commentary explores the relationship between Health Technology Assessment (HTA) and Health Benefits Package (HBP) design to achieve Universal Health Coverage (UHC) in low- and middle-income countries. It emphasizes that while HTA evaluates individual healthcare interventions, HBP reform aims to create comprehensive service sets considering overall population health needs and available resources. Challenges in LMICs include limited local data and technical capacity, leading to reliance on cost-effectiveness estimates from other settings. We suggest a practical approach by combining HTA and HBP elements through a hybrid or compartmentalized method. This approach sets differentiated cost-effectiveness thresholds for specific healthcare platforms or programs (e.g., primary care or essential surgery), aligning priority-setting with organizational considerations, ethics, and implementation strategies. Strong institutions and academic support are vital for evidence-informed priority-setting processes. In summary, HTA can play a pivotal role in designing HBPs for UHC in LMICs, and a compartmentalized approach can enhance priority-setting while considering budget constraints and equity.